A novel self-templating strategy for facile fabrication of monodisperse polymeric microporous capsules with a tunable hollow structure. Issue 18 (19th April 2021) - Tan, Liangxiao; Tan, Bien
Abstract : The self-templating fabrication of monodisperse polymeric microporous capsules with a tunable hollow structure for gas storage, efficient iodine capture and heterogeneous catalysis. Abstract : Herein, a self-templating strategy is presented for the fabrication of monodisperse microporous hollow capsules (SMHCs). Compared with other templating methods, which are normally tedious and complicated, this strategy is facile and versatile, enabling feasible control over the particle size and hollow cavity of the capsules. With a hierarchical porous structure and high surface area (965 m 2 g −1 ), these SMHCs are expected to be excellent adsorbents for gas storage (H2 of 1.09 wt% at 77 K/1.13 bar and CO2 of 10.5 wt% at 273 K/1.13 bar) and the efficient capture of iodine (413 wt%). Moreover, the functionalization of SMHCs can be readily achieved by using this strategy, which endows the functionalized (F)-SMHCs with a superior performance for 4NP reduction after immobilizing gold nanoparticles.